Cemented or cementless total knee arthroplasty? - Prudhon Jean-Louis; Verdier Régis (SICOT-J, 2017)
Introduction: Since 1996 we have been using cementless fixation with hydroxyapatite (HA) coating. The purpose of this paper is to compare survivorship of a series of 100 cemented Total Knee Arthroplasty (TKA) to a similar series of 100 cementless with a follow up of 11–16 years.